Lipid content and fatty acid composition during early and late embryonic development of redclaw crayfish, Cherax quadricarinatus (Crustacea, decapoda) - Alimon, A.R.; Roustaian, Paymon; Saad, C.R.; Kamarudin, M.S. (Blackwell Verlag, 2003)
[No abstract available]